Application of Python Scientific computing library and Simulation in Circuit Analysis - Zhang, Hong; Yang, Ping; Niu, Yali (Proceedings (International Conference on Communication Systems and Network Technologies Online), 2023)
Complicated manual calculation and drawing often appear in circuit analysis, which brings difficulty to circuit analysis. Manual ways to analysis of the circuit is timeconsuming and laborious, and prone to errors. Python can solve the problem better in circuit analysis instead of manual ways. Python is a high-level, general-purpose interpreted programming language that is widely used in scientific computing and engineering. It also includes a vast collection of Python packages for scientific computing. This ecosystem of scientifically oriented libraries ranges from generic core libraries- such as NumPy, SciPy, and Matplotlib -to more specific libraries for particular problem domains [1]. 1So Python has many applications in circuit analysis, such as equation solving, curve drawing, logic calculation and so on. In this paper, we apply Sympy library of Python to solve the equations of branch current method, use Matplotlib library to draw the sinusoidal AC signal curve, and use programming language of Python to realize the design of logic which is also the realization of logic functions. With the rapid development of computer technology, the application of new technology and software tools in circuit analysis will greatly improve the efficiency of circuit analysis.